PROFIL KEMAMPUAN PENYELESAIAN MASALAH SISWA PADA MATERI BELAH KETUPAT DI KELAS VII SMPN 6 BANAWA DI TINJAU DARI PERBEDAAN JENIS KELAMIN - Nur Adila Apriani; Awuy, Evie; Pathuddin, Pathuddin (Universitas Tadulako, 2022)
The purpose of this study was to obtain a description of students' problem-solving abilities on rhombus material in class VII SMPN 6 Banawa in terms of gender differences. This study uses a qualitative method with a qualitative descriptive approach based on the problem solving steps proposed by Polya. The results of this study indicate that male and female subjects in solving mathematical problems on rhombus material are as follows. (1) in understanding the problem, male and female subjects read the problem repeatedly, to determine what is known and asked in the question. (2) in planning problem solving, male and female subjects have the same solution, namely by assuming and using the formula for the area of ​​a rhombus. (3) in carrying out the problem-solving plan, male and female subjects solved the problem according to the plan that had been made previously, namely by using the formula for the area of ​​a rhombus but the male subject could not find the final answer. (4) in re-examining the answers of male and female subjects, write down how to check answers, using the substitution method, namely substituting the value obtained into the rhombus formula if there is a similarity in the results between the left and right sides then the answer is considered correct but the subject is male. unable to re-check the answers obtained, this is because male subjects cannot solve the problems given.